(3JMaI GdWdGH HTQM JMQjQ JfbjM GddHGHs - (3GdSfjcj, GdeUQj, GdTGaYqj, CHh jMji, TjN GdESdGe, RcQjG Hf eMeO Hf CMeO Hf RcQjG, J (B926 (3g`s ((3eMeO Hf YHO Gddg GdZGUfj GdTGaYjs)
(3ChdgG (B:s
(3HYO GdHSedI ; hHg fSJYjf hUdi Ydi SjOfG eMeO hYdi Bdg hUMHg hSde bGd SjOfG RcQjG GdCfUGQj GdTGaYj GdMeO ddg GdPj abg aj Ojfg ef GUWaGg ef GdCfGe hgOG ef GQJVGg dage eG TQYg ef GdCMcGes
(3BNQgG (B:s
(3hCMO CUhdg eSde aeSde JHYG hGdESdGe jYdh hPcQ gPg hdh cGf CMO CHhjg eQJOG hGdBNQ cGaQG CUdjG acGaQ CUdj bGdg GdHZhj hGddg CYde Je gPG GdTQM GdeHGQcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 46s
(3eYLe GdeDdajf (B1 / 733s
(3cTa GdXfhf (B2 / 1542s
(3TPQGJ GdPgH (B8 / 134s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs